2021
DOI: 10.1111/pai.13510
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune manifestations among 461 patients with monogenic inborn errors of immunity

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
(148 reference statements)
0
1
1
Order By: Relevance
“…In our cohort, we have one patient with ICOS deficiency in 34 CVID patients (2.9%). Recent studies showed that pediatric CVID patients, especially who have autoimmune disorders, mostly mutated with autoimmune-associated genes like LRBA and AIRE [34]. Although 42% of our patients have at least one autoimmune disorder, we did not detect any pathogenic variant in autoimmune-related genes.…”
Section: Discussioncontrasting
confidence: 69%
“…In our cohort, we have one patient with ICOS deficiency in 34 CVID patients (2.9%). Recent studies showed that pediatric CVID patients, especially who have autoimmune disorders, mostly mutated with autoimmune-associated genes like LRBA and AIRE [34]. Although 42% of our patients have at least one autoimmune disorder, we did not detect any pathogenic variant in autoimmune-related genes.…”
Section: Discussioncontrasting
confidence: 69%
“…S2G). Given that thyroid autoimmunities are among the most common endocrine autoimmune features in the clinic and enriched in IEIs with autoimmunity (33), our results indicate that the AutoCore is linked through the transcription machinery across various tissue types but most prominently in immune cell-related tissues. Together, these results demonstrate that the AutoCore represents major molecular, phenotypic, and therapeutic hallmarks of autoimmune/autoinflammatory diseases, suggesting that network-based methods can be further applied to identify disease subclusters and therapeutic options.…”
Section: Identification Of the Autocore A Dense Interactome Subnetwor...mentioning
confidence: 83%